If We Had Wings We Would Fly to You : a Soviet Jewish Family Faces Destruction, 1941-42. - Feferman, Kiril (Jews of Russia and Eastern Europe and Their Legacy Ser., 2020)
This is the first work in any language that offers both an overarching exploration of the flight and evacuation of Soviet Jews viewed at the macro level, and a personal history of one Soviet Jewish family. The book makes a significant contribution to the history of the Holocaust and Second World War in the Soviet Union, presenting one Soviet region as an illustration of wartime social and media politics.